1990
DOI: 10.1200/jco.1990.8.5.784
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation in B-cell non-Hodgkin's lymphoma: very low treatment-related mortality in 100 patients in sensitive relapse.

Abstract: One hundred patients with B-cell non-Hodgkin's lymphoma (NHL) in sensitive relapse or incomplete first remission underwent high-dose chemoradiotherapy and anti-B-cell monoclonal antibody (MAb)-treated autologous bone marrow transplantation (ABMT). These patients demonstrated good performance status with a Karnofsky score of 80% or greater. The majority of these patients had one or more adverse prognostic features including a failure to achieve a complete remission (CR) with conventional combination chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(50 citation statements)
references
References 22 publications
3
45
1
1
Order By: Relevance
“…However, our transplant-related mortality rate (9%) is slightly higher than the reported average early treatmentrelated mortality of 5% or less. 19,20 On the other hand, we have not observed any cases of secondary myelodysplasia (MDS) or treatment-related AML during a median followup period of 29 months after transplantation. Some studies have shown a relatively high incidence of secondary MDS as a late complication of autologous SCT with relative risk as high as to 18% at 6 years.…”
Section: Discussionmentioning
confidence: 88%
“…However, our transplant-related mortality rate (9%) is slightly higher than the reported average early treatmentrelated mortality of 5% or less. 19,20 On the other hand, we have not observed any cases of secondary myelodysplasia (MDS) or treatment-related AML during a median followup period of 29 months after transplantation. Some studies have shown a relatively high incidence of secondary MDS as a late complication of autologous SCT with relative risk as high as to 18% at 6 years.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies include only a minority of patients with low-grade lymphoma among patients with intermediate-or high-grade lymphoma. 13,14,30,31 Studies of low-grade lymphoma may include several histologic types of lymphoma with different natural histories, such as mixed cell lymphoma (large cleaved cell lymphoma 5,6,11 and unrecognized cases of mantle cell lymphoma. It is in this context that we report our experience with 51 patients who received autologous or allogeneic transplantation as salvage therapy for documented SCCL.…”
Section: Discussionmentioning
confidence: 99%
“…These transplant protocols have been published. [10][11][12][13][14] Quality of life instruments Patients were surveyed by mail before hospital admission and at 6 and 12 months post HCT. The survey solicited qualitative information on symptoms, self-assessment of health, feelings about the transplantation procedure and sense of recovery after transplantation.…”
Section: Patientsmentioning
confidence: 99%